Faith and feminism in nineteenth-century religious communities - Sohn-Kronthaler, Michaela, 1969-; Albrecht, Ruth (Bible and women, 2019)
"This latest volume in the Bible and Women series is concerned with documenting, in word and image, well-known and largely unknown women and their relationship to the Bible from the period of the late eighteenth century up to the beginning of the twentieth century. Women authors from this period are presented along with their explanations and interpretations. The essays in this collection prove the diversity of feminine reading of the Bible and the broad range of treatment of the Holy Scripture. Paul Chilcote, Marion Ann Taylor, Christiana de Groot, Elizabeth M. Davis, and Pamela S. Nadell offer perspectives on the Anglo-American sphere during this period. Marina Cacchi, Adriano Valerio, and Inmaculada Blasco Herranz, as well as by Alexei Klutschewski and Eva Maria Synek illuminate the areas of southern and eastern Europe. Angela Berlis, Ruth Albrecht, Doris Brodbeck, Ute Gause, and Michaela Sohn-Kronthaler examine women from the German-speaking world and their texts. Bernhard Schneider, Magda Motté, Katharina Büttner-Kirschner, and Elfriede Wiltschnigg treat the subject area of religious literature and art"--